1996
DOI: 10.3346/jkms.1996.11.1.88
|View full text |Cite
|
Sign up to set email alerts
|

Uterine endometrial stromal sarcoma with rhabdoid and smooth muscle differentiation

Abstract: Uterine and extrauterine tumors composed of cells featuring endometrial stromal cells often show ovarian sex cord-like structures and smooth muscle differentiation. A few cases of endometrial stromal tumors showing rhabdoid differentiation have been reported. The present case is a 20-year-old woman with endometrial stromal sarcoma that had sex cord-like structures, smooth muscle components and rhabdoid differentiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 0 publications
1
18
0
Order By: Relevance
“…World Health Organization distinguished these neoplasms from ESTs (12); however, we consider as some others these rare neoplasms to be variants of ESTs that are derived from multipotential uterine mesenchymal cells that have the capacity for differentiation along endometrial stromal, sex cord, epithelial or myoid lines [4,6,10,13,17]. Our data support that this unusual uterine tumor is a polyphenotypic neoplasm with true sex cord differentiation, from a derivative of the Müllerian tract.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…World Health Organization distinguished these neoplasms from ESTs (12); however, we consider as some others these rare neoplasms to be variants of ESTs that are derived from multipotential uterine mesenchymal cells that have the capacity for differentiation along endometrial stromal, sex cord, epithelial or myoid lines [4,6,10,13,17]. Our data support that this unusual uterine tumor is a polyphenotypic neoplasm with true sex cord differentiation, from a derivative of the Müllerian tract.…”
Section: Discussionsupporting
confidence: 56%
“…Morphologic and immunohistochemical findings indicate that UTROSCT arise from pluripotent mesenchymal cells, which predominantly differentiate into sex cord cells [5,6]. Besides endometrial stromal cells, smooth and skeletal muscle and epithelial or clear cell differentiation can also occur [4,6,13]. Here we described the clinical, histological and immunohistochemical features of a rare case of UTROSCT, discussed the diagnostic difficulties and possible neoplastic origin.…”
Section: Introductionmentioning
confidence: 94%
“…The presence of conventional endometrial stromal neoplasia, the absence of typical areas of smooth muscle neoplasm or nerve sheath differentiation as well as immunohistochemical stains will help in these differential diagnoses. 7,18 Other unusual morphologic features reported in ESTs that were not identified in our cases included cells with granular eosinophilic cytoplasm, 15,20 rhabdoid phenotype, 9,13,24,28 and clear cell change. 11 Herein we describe the presence of bizarre nuclei in an EST, a feature not previously emphasized in the literature.…”
Section: Discussionmentioning
confidence: 60%
“…Chu and Arber (8) demonstrated that 3 (60%) of 5 extrauterine rhabdomyosarcomas were also positive for CD10, suggesting CD10 expression is not restricted to rhabdomyoblastic cells in uterine tumors. On the other hand, the intimate relationship between endometrial stroma and skeletal muscle differentiation is suggested by the rare examples of stromal nodule with skeletal muscle differentiation (35), ESS with rhabdoid differentiation (36), and adenomyofibroma with skeletal muscle differentiation (37). Therefore, CD10 expression might be a common phenotypic characteristic suggesting mül-lerian derivation of rhabdomyoblastic cells, although this subject requires further studies and assessment.…”
Section: Discussionmentioning
confidence: 99%